DIFFERENCE Of THE IMC BETWEEN STUDENTS OF PUBLIC AND PRIVATE SCHOOL (Fiep Bulletin - online, 2015)
Overweight and infantile obesidade present high prevalence of multifactorial character, whose development on biological, psychological influence of factors and economic partner. With the objective to evaluate the difference Index of Corporal Mass (IMC) of pupils of Public and Private Schools, transversal cut with 40 pupils of 14 years was carried through, of the cited institutions of the urban zone of the city of Lafaiete Council member, MG. The evaluation was carried through in the rooms of the respective institutions, in which the pupils studied, where to get the longed for results they had been collected the weight and height of these pupils who had been applied formulates it of the IMC. The group through the directors of the schools, emitted a letter to responsible of the students of both the schools, so that the same ones had a knowledge of the objectives of the research.Overweight and obesidade had been defined as index of bigger corporal mass that determined for the age and the sex. It analyzes it of the carried through research, determined the influence of the factors in question. In conclusion it has influence of biological and ambient factors in the development of the overweight and infantile obesidade, what it led to the waited result of that the IMC of students of private school to be bigger of the one than of pupils of schools you publish.
Keywords: ICM; Obesity; Children